Spanish validation of the Body Responseveness Connection Scale in medical residents at San Rafael de Tunja Hospital in Colombia - Alba Maldonado, Juan Carlos (2021)
The connection between mind and body refers to the process of self-regulation therapies designed to increase both physical and mental well-being. Objective: To determine the psychometric properties of the Body Responsiveness Connection Scale  in a population of medical interns and residents  at the San Rafael Hospital in the city of Tunja (Colombia). Material and methods: A translation and back translation of the Body Responseveness Connection Scale was performed. The instrument was applied to 112 resident physicians of the San Rafael de Tunja Hospital, between the ages of 18 and 35. The internal consistency of the instrument was analyzed using Cronbach’s α, and the test-retest reliability with intraclass correlation coefficient. Results: The average age of the participants was 23.5  years (SD ± 2.06 years), the majority were women. 38.4% came from public universities and 62.4% reported no additional activities in their free time. The internal consistency of the scale was 0.87. The correlation coefficient was greater than 0.6 in most of the items. Conclusions: The studied body response scale in health personnel presents psychometric properties similar to the original version, with adequate reliability and validity, which allow the evaluation of relevant aspects of body awareness and dissociation.